British Military Withdrawal and the Rise of Regional Cooperation in South-East Asia, 1964-73 - Thompson, S. author. aut Link
VII, 193 p.
Keywords: This book examines the links between Britain's withdrawal from its east of Suez role and the establishment of South-East Asian regional security arrangements. The link between these two events is not direct, but a relationship existed, which is important to a wider understanding of the development of regional security arrangements.